2010
DOI: 10.1371/journal.pone.0011131
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Potential Role of Muscle Spindle Mechanoreceptor Afferents in Chronic Muscle Pain in the Rat Masseter Muscle

Abstract: BackgroundThe phenotype of large diameter sensory afferent neurons changes in several models of neuropathic pain. We asked if similar changes also occur in “functional” pain syndromes.Methodology/Principal FindingsAcidic saline (AS, pH 4.0) injections into the masseter muscle were used to induce persistent myalgia. Controls received saline at pH 7.2. Nocifensive responses of Experimental rats to applications of Von Frey Filaments to the masseters were above control levels 1–38 days post-injection. This effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
90
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(93 citation statements)
references
References 93 publications
(115 reference statements)
3
90
0
Order By: Relevance
“…Wu et al (2004) reported the presence of VGluT1 in the muscle spindles of rat triceps surae muscle. In the trigeminal system, the muscle spindles of the rat masseteric nerve displayed VGluT1 immunoreactivity that originated from the trigeminal mesencephalic nucleus neurons (Pang et al, 2006, Lund et al, 2010. Thus, it is safe to say that VGluT1 present in the nerve endings originates from medium-large neurons, because muscle spindles are innervated by medium-large sensory neurons.…”
Section: Vglut In Ruffini Endingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Wu et al (2004) reported the presence of VGluT1 in the muscle spindles of rat triceps surae muscle. In the trigeminal system, the muscle spindles of the rat masseteric nerve displayed VGluT1 immunoreactivity that originated from the trigeminal mesencephalic nucleus neurons (Pang et al, 2006, Lund et al, 2010. Thus, it is safe to say that VGluT1 present in the nerve endings originates from medium-large neurons, because muscle spindles are innervated by medium-large sensory neurons.…”
Section: Vglut In Ruffini Endingsmentioning
confidence: 99%
“…In addition, the presence of VGluT has been documented in the peripheral endings of neurons in the dorsal root and trigeminal ganglion. In the trigeminal nervous system, muscle spindles of jaw closer display VGluT1 immunoreactivity (Pang et al, 2006;Lund et al, 2010). This originates from neurons in the trigeminal mesencephalic nucleus showing immunoreactivity for VGluT1 (Pang et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Removal of substances which accumulate into the gel-filled periaxial space of the muscle spindle is a slow process. The sensory innervation of a muscle spindle consists of primary and secondary endings [13], and also IIIand IV-afferents [16][17][18][19]. Also, autonomic innervation has been observed [19,20].…”
Section: Structure Vascular Supply and Innervation Of The Muscle Spimentioning
confidence: 99%
“…Trigger points comprise inflamed and painful muscle spindles with overactive nociceptive afferents. There are somatic thin nerve axons inside the muscle spindle and in its capsule [19]. Thus, it is also conceivable that pain spots in routine EMG of healthy muscles [1] are in fact muscle spindles.…”
Section: Trigger Points Taut Bands and Pain Spotsmentioning
confidence: 99%
See 1 more Smart Citation